A comprehensive performance evaluation of MIPv6 and PMIPv6 mobility management protocols in wireless mesh network - Hoh, Wei Siang; Yoon, Si-Kee; Ong, Bi-Lynn; Ahmad, R. Badlishah (Faculty of Electrical Engineering, Computer Science and Information Technology, Josip Juraj Strossmayer University of Osijek, 2021)
Wireless communication is becoming essential due to the dramatic increase in the usage of mobile devices. The high demand for real-time or instant services requires wireless Internet networks which can support different Quality of Service (QoS) guarantees and different traffic characteristics. All Internet network mobile device services are supported by mobility management protocols. In this paper, we compare the performance of the MIPv6 and PMIPv6 mobility management protocols in the Wireless Mesh Network (WMN) environment. We identify and analyze the MIPv6 and PMIPv6 mobility management protocols' characteristics by using performance indicators. The performance comparison of MIPv6 and PMIPv6 mobility management protocols was conducted in terms of throughput, latency, and packet loss ratio. Based on the conducted experimental results, we summarize the performances for MIPv6 and PMIPv6 mobility management protocols in the Wireless Mesh Network environment. The results obtained indicate that PMIPv6 generally outperforms MIPv6. In future work, the evaluation of HMPIv6, FMIPv6, and FHMIPv6 is proposed.